Inclusive growth and leading sector in Bali - Ni Made Ayu Krisna Cahyadi; Sasongko Sasongko; Putu Mahardika Adi Saputra (Universitas Islam Indonesia, 2018)
This research analyzes the dynamics of pro-poor growth in 9 regencies/cities of Bali province from 2007 to 2015. This research identifies pro-poor growth based on Poverty Equivalent Growth Rate (PEGR). The results show that the regions with agriculture leading sector tend to have pro-poor growth in reducing poverty and inequality but anti-poor in absorbing labors. On the contrary, the regions with high tourism potential show anti-poor growth trend in reducing poverty and inequality but pro-poor in absorbing labors.